Historic drought in northern Kenya shifts diet and mobility away from traditional pastoralism as resource security and nutrition falter - Asher Y. Rosinger; Matthew Douglass; Amanda McGrosky; Kedir Teji Roba; Benjamin Davies; Natalie Meriwether; Alfredo J. Rojas; Leslie Ford; Hannah Jacobson; Faith Wambua; Elena Hinz; Srishti Sadhir; et al. (Global Environmental Change, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Advancing participatory sensing and knowledge production methods for city air quality governance: Applying the Breathe London Community Programme model - Kayla Schulte; Andrew Grieve; Benjamin Barratt; Timothy Baker; Hima Coonjobeeharry; Mohammed Mead (Environmental Science & Policy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The AGN-201 Digital Twin: A test bed for remotely monitoring nuclear reactors - Ryan Stewart; Eduardo Treviño; Ashley Shields; Kolton Heaps; John Darrington; Quinton Williams; Chad Pope; Johnathan Scott; Benjamin Baker; Jaden Palmer; Benoni Vainqueur; Todd S. Palmer; et al. (Annals of Nuclear Energy, 2025)

Nutrient limitation and seasonality associated with phytoplankton communities and cyanotoxin production in a large, hypereutrophic lake - Gabriella M. Lawson; Jakob L. Young; Zachary T. Aanderud; Erin F. Jones; Samuel Bratsman; Jonathan Daniels; Madeleine P. Malmfeldt; Michelle A. Baker; Benjamin W. Abbott; Scott Daly; Hans W. Paerl; Greg Carling; et al. (Harmful Algae, 2025)

Stand structure and disturbance history of old-growth blue pine (Pinus wallichiana) forests in the Bhutan Himalaya - Karma Tenzin; Craig R. Nitschke; Kathryn J. Allen; Benjamin Wagner; Thiet V. Nguyen; Patrick J. Baker (Dendrochronologia, 2024)

Atlas of pacific sand lance (Ammodytes personatus) benthic habitat – Application of multibeam acoustics and directed sampling to identify viable subtidal substrates - Matthew R. Baker; H. Gary Greene; John Aschoff; Elisa Aitoro; Eileen Bates; Donovan Hesselroth; Katie Johnson; Benjamin Mather; Nancy Sealover (Marine Environmental Research, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Lunar Flashlight science ground and flight measurements and operations using a multi-band laser reflectometer - Barbara A. Cohen; Ryan R. Petersburg; Daniel R. Cremons; Patrick S. Russell; Paul O. Hayne; Benjamin T. Greenhagen; David A. Paige; Jose Martinez Camacho; Nathan Cheek; Mark T. Sullivan; Valeria Lopez Robles; Jessica Ban; et al. (Icarus, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Evaluation of Digital Drawing Tests and Paper-and-Pencil Drawing Tests for the Screening of Mild Cognitive Impairment and Dementia: A Systematic Review and Meta-analysis of Diagnostic Studies - Joyce Y. C. Chan; Baker K. K. Bat; Adrian Wong; Tak Kit Chan; Zhaohua Huo; Benjamin H. K. Yip; Timothy C. Y. Kowk; Kelvin K. F. Tsoi (Neuropsychology Review, 2022)
Digital drawing tests have been proposed for cognitive screening over the past decade. However, the diagnostic performance is still to clarify. The objective of this study was to evaluate the diagnostic performance among different types of digital and paper-and-pencil drawing tests in the screening of mild cognitive impairment (MCI) and dementia. Diagnostic studies evaluating digital or paper-and-pencil drawing tests for the screening of MCI or dementia were identified from OVID databases, included Embase, MEDLINE, CINAHL, and PsycINFO. Studies evaluated any type of drawing tests for the screening of MCI or dementia and compared with healthy controls. This study was performed according to PRISMA and the guidelines proposed by the Cochrane Diagnostic Test Accuracy Working Group. A bivariate random-effects model was used to compare the diagnostic performance of these drawing tests and presented with a summary receiver-operating characteristic curve. The primary outcome was the diagnostic performance of clock drawing test (CDT). Other types of drawing tests were the secondary outcomes. A total of 90 studies with 22,567 participants were included. In the screening of MCI, the pooled sensitivity and specificity of the digital CDT was 0.86 (95% CI = 0.75 to 0.92) and 0.92 (95% CI = 0.69 to 0.98), respectively. For the paper-and-pencil CDT, the pooled sensitivity and specificity of brief scoring method was 0.63 (95% CI = 0.49 to 0.75) and 0.77 (95% CI = 0.68 to 0.84), and detailed scoring method was 0.63 (95% CI = 0.56 to 0.71) and 0.72 (95% CI = 0.65 to 0.78). In the screening of dementia, the pooled sensitivity and specificity of the digital CDT was 0.83 (95% CI = 0.72 to 0.90) and 0.87 (95% CI = 0.79 to 0.92). The performances of the digital and paper-and-pencil pentagon drawing tests were comparable in the screening of dementia. The digital CDT demonstrated better diagnostic performance than paper-and-pencil CDT for MCI. Other types of digital drawing tests showed comparable performance with paper-and-pencil formats. Therefore, digital drawing tests can be used as an alternative tool for the screening of MCI and dementia.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Decarbonization and its discontents: a critical energy justice perspective on four low-carbon transitions - Benjamin K. Sovacool; Mari Martiskainen; Andrew Hook; Lucy Baker (Climatic Change, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The Navy Global Environmental Model - Timothy Hogan; Ming Liu; James Ridout; Melinda Peng; Timothy Whitcomb; Benjamin Ruston; Carolyn Reynolds; Stephen Eckermann; Jon Moskaitis; Nancy Baker; John McCormack; Kevin Viner; et al. (Oceanography, 2014)

Does spatial resolution matter? A multi-scale comparison of object-based and pixel-based methods for detecting change associated with gas well drilling operations - Benjamin A. Baker; Timothy A. Warner; Jamison F. Conley; Brenden E. McNeil (International Journal of Remote Sensing, 2013)

Hydrologic control of nitrogen removal, storage, and export in a mountain stream - Robert Jr. O. Hall; Michelle A. Baker; Christopher D. Arp; Benjamin J. Koch (Limnology and Oceanography, 2009)
Nutrient cycling and export in streams and rivers should vary with flow regime, yet most studies of stream nutrient transformation do not include hydrologic variability. We used a stable isotope tracer of nitrogen ( 15 N) to measure nitrate (NO 3 − ) uptake, storage, and export in a mountain stream, Spring Creek, Idaho, U.S.A. We conducted two tracer tests of 2‐week duration during snowmelt and baseflow. Dissolved and particulate forms of 15 N were monitored over three seasons to test the hypothesis that stream N cycling would be dominated by export during floods, and storage during low flow. Floods exported more N than during baseflow conditions; however, snowmelt floods had higher than expected demand for NO 3 − because of hyporheic exchange. residence times of benthic N during both tracer tests were longer than 100 d for ephemeral pools such as benthic algae and wood biofilms. Residence times were much longer in fine detritus, insects, and the particulate N from the hyporheic zone, showing that assimilation and hydrologic storage can be important mechanisms for retaining particulate N. Of the tracer N stored in the stream, the primary form of export was via seston during periods of high flows, produced by summer rainstorms or spring snowmelt the following year. Spring Creek is not necessarily a conduit for nutrients during high flow; hydrologic exchange between the stream and its valley represents an important storage mechanism.

Historical transoceanic dispersal of a freshwater shrimp: the colonization of the South Pacific by the genus Paratya (Atyidae) - Timothy J. Page; Andrew M. Baker; Benjamin D. Cook; Jane M. Hughes (Journal of Biogeography, 2005)
Aim To infer the phylogenetic relationships within the freshwater shrimp genus Paratya Miers, 1882 (Atyidae) and to use these data to answer biogeographical questions about the location, timing and form of evolution of this genus in the South Pacific. Location Paratya are spread throughout various freshwater habitats in the western Pacific, with a disjunct northern range in the North Pacific (Japan, Korea, Ryukyu Islands, Siberia) and South Pacific (Australia, New Zealand, New Caledonia, Lord Howe, Norfolk Island). Methods Specimens were obtained from throughout its range. Mitochondrial sequences of cytochrome oxidase subunit I and 16S ribosomal DNA were analysed using phylogenetic techniques to identify whether landmasses are monophyletic and what the relationships are between landmasses. Molecular clock dating methods were used to date divergences between taxa. Results Each landmass was recovered as monophyletic. Japan/Ryukyu Islands is the most basal group, followed by New Zealand. Australian specimens form a sister group to a clade made up of two groups (New Caledonia and Lord Howe/Norfolk Island). The oldest divergence within the genus (between North and South Pacific) took place 12 –19 Ma. Main conclusions The geographical origin of the genus (either Gondwana or Laurasia) is unclear. Dispersal occurred between the North and South Pacific long after the split up of Gondwana. Dispersal likely explains the presence of Paratya on each landmass in the South Pacific, from continent to isolated oceanic island. This dispersal is conjectured to have taken place through oceanic currents because of the amphidromous life cycle of some taxa of Paratya , given that amphyidromy is plesiomorphic in atyid shrimp.

Analysis and glycosyl composition of the exopolysaccharide isolated from the floc‐forming wastewater bacterium Thauera sp. MZ1T - Michael S. Allen; Karen T. Welch; Benjamin S. Prebyl; David C. Baker; Arthur J. Meyers; Gary S. Sayler (Environmental Microbiology, 2004)
Summary Conditions were developed for the reproducible production, isolation and characterization of a novel microbial extracellular polysaccharide believed to be involved in transient viscous bulking at an industrial wastewater treatment plant. The exopolysaccharide was extracted from cell‐free culture supernatants of Thauera sp. strain MZ1T grown on a minimal medium with succinate. The purified polymer was found to be approximately 260 kDa in size by gel‐permeation chromatography. The GC–MS analysis of the alditol acetate and per‐ O ‐trimethylsilyl methyl glycoside derivatives revealed that the exopolysaccharide was composed of four monosaccharides including: rhamnose, galacturonic acid, N ‐acetylglucosamine and N ‐acetylfucosamine. Glucose, which also appeared at low levels, is most likely from a co‐eluting glucan. The FTIR and NMR spectroscopic analyses further revealed the presence of esterified component groups on the polymer. These results represent the first published description of a polysaccharide from a member of the genus Thauera , and lay the foundation for a deeper understanding of the factors potentially involved in zoogloeal cluster formation and viscous bulking.

Microbiological, molecular biological and stable isotopic evidence for nitrogen fixation in the open waters of Lake Michigan - Barbara J. MacGregor; Benjamin Van Mooy; Brett J. Baker; Mark Mellon; Pia H. Moisander; Hans W. Paerl; Jonathan Zehr; David Hollander; David A. Stahl (Environmental Microbiology, 2001)
We have used a combination of microbiological, molecular biological and stable isotope methods to relate specific microbial populations to elemental cycling at an offshore site in Lake Michigan. Several lines of evidence suggest that atmospheric N 2 may be a significant source of nitrogen to the lake. Particulate organic nitrogen (PON) at ≈ 10–15 m depth in July and October had a δ 15 N of 0.5–1.5‰. These values closely reflect the 15 N composition of atmospheric N 2 , suggesting biological nitrogen fixation. Historical data show a developing late‐summer N:P minimum at ≈ 15 m; low abundance of inorganic nitrogen relative to phosphorus favours species able to acquire atmospheric nitrogen. Microscopic examination of October water samples revealed abundant heterocystous cyanobacteria, including Nodularia sp. Potentially nitrogen‐fixing Anabaena spp. have been found in Lake Michigan before but, to our knowledge, this is the first report of Nodularia . Finally, we have amplified both cyanobacterial and non‐cyanobacterial nifH sequences (encoding the nitrogenase iron protein) from lakewater samples, evidence for the presence of bacteria capable of nitrogen fixation. The surface waters of Lake Michigan are considered to be phosphate limited in the stratified season and, under these conditions, energetically expensive nitrogen fixation is expected to be uncompetitive with assimilation of combined nitrogen. Our results suggest that, from both microbiological and biogeochemical perspectives, this may be an oversimplification.

Toxicology of various pesticides and their decomposition products on mitochondrial electron transport - Ronald S. Pardini; James C. Heidker; Theresa A. Baker; Benjamin Payne (Archives of Environmental Contamination and Toxicology, 1980)